2022
DOI: 10.47197/retos.v44i0.91163
|View full text |Cite
|
Sign up to set email alerts
|

Lesiones deportivas en el fútbol en personas con discapacidad visual. Revisión sistemática exploratoria (Sport injuries in football for individuals with visual impairment. Exploratory systematic review)

Abstract: El presente estudio tiene como objetivo realizar una revisión sistemática exploratoria relacionada con las lesiones en el fútbol a 5 en personas con discapacidad visual. Para la búsqueda de documentos, se emplearon las siguientes palabras clave: “Football 5-a-side” e “Injury”. Las bases de datos utilizadas fueron Web Of Science, Pubmed y Scopus. Para limitar la búsqueda de manuscritos, se establecieron una serie de criterios de inclusión y exclusión con la finalidad de seleccionar documentos adecuados. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 13 publications
(35 reference statements)
0
4
0
3
Order By: Relevance
“…The aim of the research was to analyse the efficiency of goal shooting in Fa5 during the international tournament WGP 2021, held in Tokyo (Japan). Considering that research works related to sports performance indicators in Fa5 are scarce in the scientific literature (Gamonales et al, 2018a;Gamonales et al, 2022), descriptive results of the present study show how players perform more shots on goal in the groups phase and during the 1st half of the games.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…The aim of the research was to analyse the efficiency of goal shooting in Fa5 during the international tournament WGP 2021, held in Tokyo (Japan). Considering that research works related to sports performance indicators in Fa5 are scarce in the scientific literature (Gamonales et al, 2018a;Gamonales et al, 2022), descriptive results of the present study show how players perform more shots on goal in the groups phase and during the 1st half of the games.…”
Section: Discussionmentioning
confidence: 59%
“…The refereeing performance or a player replacing during the game, can have a significant effect on the game (Caballero et al, 2017;Lago-Peñas et al, 2010). Other causes are the technical-tactical demands of Fa5 (Morato et at., 2011), efficiency in guiding orientation (Suárez, 2014), team travel to match venues (García-Rubio et al, 2014), sports injuries (Gamonales et al, 2022), and even accumulated fatigue from playing several matches in short spans of time (Gamonales, Muñoz-Jiménez, Mancha-Triguero et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the assessment of children with CP it was found that muscle synergy analysis has a great potential in the assessment of motor dysfunction and that robotic technology may be used to quantify complex and discrete aspects of upper limb sensory and motor function (Gamonales, Jiménez-Solis, Gámez-Calvo, Sánchez-Ureña, & Muñoz-Jiménez, 2022). Consistent with the shift of focus on impairments of children with CP, new outcome measures have been developed to focus on function and ability (Debuse & Brace, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…En la literatura científica, existen diferentes procedimientos de búsqueda de documentos, pero en el contexto del deporte y la discapacidad, destaca el desarrollado por Gámez-Calvo et al, (2020), Gamonales et al, (2022), y/o Gamonales et al, (2018), en sus respectivas revisiones, por ser un proceso metodológico sencillo, intuitivo y fácil de usar. El éxito de una búsqueda de literatura reside en llevar a cabo una planificación de las fases a seguir (Thomas et al, 2015).…”
Section: Procedimiento De Registro Para Los Estudiosunclassified